[Burden of Short Bowel Syndrome in Italy: Direct and Indirect Costs and Quality of Life] - Mennini, Francesco Saverio; Bini, Chiara; Paoletti, Martina; Marcellusi, Andrea; Sciattella, Paolo; Viti, Raffaella; Amoroso, Lucrezia; Fioravanti, Laura; Di Martino, Gennaro; Ragonese, Angela; et al. (Farmeconomia. Health economics and therapeutic pathways, 2023)
OBJECTIVE: The Short Bowel Syndrome (SBS) is the most common cause of chronic intestinal failure (CIF) due to benign disease. The prevalence in Europe was estimated about 1.4 cases per million and few information are available for Italy. Home parenteral nutrition (HPN) is the primary and lifesaving treatment for patients with CIF. The parenteral nutrition (PN) has a great impact on the quality of life (QoL) of patients and the role of the caregiver is crucial for the disease management. The aim of this study was to evaluate the economic burden of SBS in Italy and to assess the impact of the disease and the parenteral nutrition on the quality of life of patients. METHODS: The total burden of SBS in Italy was assessed both in terms of costs and QoL using different tools. A prevalence-based cost of illness (COI) model was developed to estimate direct costs (PN cost, central venous catheter insertion cost, monitoring cost, hospitalization cost) and indirect costs (absenteeism, presenteeism, unemployment, abandonment of work due to the disease and economic benefits granted by the National Social Security Institute) associated with patient with SBS in Italy. The total annual costs were calculated considering a micro-costing approach, thus associating the average costs per patient with the prevalence of the disease. A systematic literature review (SLR) was conducted to collect epidemiological and direct cost data related to the patients with SBS. Hospital costs were estimated using the national Hospital Information System. Indirect costs were estimated using a human capital approach; therefore, the productivity loss was estimated both for patients and caregivers. A survey was conducted to obtain data about productivity loss and quality of life of patients and caregivers. The questionnaires were completed by clinicians, who were asked to indirectly report the experience of patients with SBS in parenteral nutrition currently being treated at their referral center. In a subsequent phase, a focus group was conducted to collect further information on QoL for patients and caregivers based on the experience of the KOLs involved. The QoL was evaluated considering a Likert scale. RESULTS: The prevalence of patients with gastrointestinal disease in HPN was estimated equal to 9.4 and 2.3 patients per million inhabitants for adults (age >18) and pediatric (age 0-18 years) patients, respectively. Knowing that SBS is the main cause of CIF due to benign disease, constituting 75% among adults and 56% among children, the number of adults with SBS in HPN present in Italy were 420, while the number of children with SBS in HPN were 77. Regarding direct costs, the mean total annual cost associated with adult and pediatric patient with SBS in Italy was estimated equal to € 36,434 and € 46,682, respectively. Parenteral nutrition accounted for 91% of the mean total cost estimated for the adult and for 87% of the mean total cost estimated for pediatric patient. Concerning indirect costs, the mean total annual cost per adult patient was estimated equal to € 51,093 (81% related to the productivity loss because of the abandonment of work due to the disease), while the mean total cost per pediatric patient was estimated equal to € 3,201 (60% related to caregiver’s presenteeism and 40% attributable to caregiver’s absenteeism). Finally, the average total annual cost per adult SBS patient in Italy was estimated at € 87,527 (42% of direct costs and 58% of indirect costs), whereas for pediatric patients it was estimated at € 49,882 (94% of direct costs and 6% of indirect costs). Overall, the weighted average cost for an SBS patient in Italy was estimated at € 81,712 (47% of direct costs and 53% of indirect costs). The analysis conducted on the QoL of patients with SBS in PN has shown that QoL was perceived as low (mean value equal to 5). The greatest impact on QoL was due to the disease (mean value equal to 9), while PN appeared to have less impact (mean value equal to 6). CONCLUSIONS: The analysis provides an estimate of the total burden associated with patients with SBS in Italy both in terms of cost and QoL. The cost associated with parenteral nutrition and indirect costs represent the main drivers of the total cost estimated for a patient with SBS in Italy. Based on the experience of the KOL involved in this study it was also found that the disease has a great impact on the QoL of these patients.